2013
DOI: 10.5296/bmh.v1i1.3401
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Awareness and Usage of Nutrition Information in Botswana

Abstract: Nutrition information enables consumers to make informed decisions when purchasing and consuming food products. Despite this, the issue of consumer awareness and usage of nutrition information has attracted little research attention in developing countries. This study presents findings of an empirical investigation of nutrition information awareness and usage in Botswana. The study is descriptive and data was collected using a structured questionnaire administered to a sample of 150 consumers in Gaborone, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
3
9
0
1
Order By: Relevance
“…We believe that the main factors have been reported in other studies such as: the food was routine/familiar to them [19], or they do not believe and do not understand the food label [18]. According to Themba & Tanjo (2013), lack of nutrition knowledge, lack of interest, do not believe nutrition information on food products, small print on labels, read nutrition information only when purchasing food items for the first time and time pressures were ranked in order of priority [21]. Surveying perception of consumers about the importance of reading information on food labels, 48.4% perceived reading food label as very important, and 36.5%…”
Section: Resultsmentioning
confidence: 97%
“…We believe that the main factors have been reported in other studies such as: the food was routine/familiar to them [19], or they do not believe and do not understand the food label [18]. According to Themba & Tanjo (2013), lack of nutrition knowledge, lack of interest, do not believe nutrition information on food products, small print on labels, read nutrition information only when purchasing food items for the first time and time pressures were ranked in order of priority [21]. Surveying perception of consumers about the importance of reading information on food labels, 48.4% perceived reading food label as very important, and 36.5%…”
Section: Resultsmentioning
confidence: 97%
“…Several demographic factors were associated with consumer label use and comprehension: education or socio-economic status, gender, family or household size, age, urban location, and ethnicity. Education level is positively associated with label use in India ( 30 32 ) , the United Arab Emirates ( 26 , 27 ), Mexico ( 35 ), Mauritius ( 43 ), and South Africa ( 44 ); socio-economic status is also positively associated with label use in Botswana ( 37 ). Gende r is a predictor of label use in studies from Malawi ( 41 ), Ghana ( 39 ), the United Arab Emirates ( 26 , 27 ), India ( 30 ), Mexico ( 35 ), Korea ( 23 ), and Singapore ( 25 ).…”
Section: Consumer Usage and Attitudes Towards Nutrition Labelling In mentioning
confidence: 99%
“…A study in Mauritius found significant label use among women but no association between gender and label understanding ( 43 ). Family and household size are positively associated with label use; consumers with larger families and those shopping for children are more likely to use the label ( 26 , 35 , 37 , 43 ), although household size was not a determinant in Pakistan ( 33 ). Age is also significant; however, age groups varied by country.…”
Section: Consumer Usage and Attitudes Towards Nutrition Labelling In mentioning
confidence: 99%
See 1 more Smart Citation
“…El sistema de semáforo nutricional puede llevar a que se discrimine el consumo de alimentos con etiqueta roja y por lo tanto se evite el consumo de grupos de alimentos esenciales para una dieta equilibrada (Hodgkins et al, 2012). Múltiples autores (Zaidi & Muhammad,2012;Themba & Tanjo, 2013)inclusive indican que los consumidores no observan la etiqueta para evaluar los componentes nutricionales del productos, sino, para analizar primero información como la fecha de caducidad, detalles del fabricante, información de seguridad, etc. Algunos consumidores incluso llegan a afirmar que leer la etiqueta de los productos es una molestia o que son el precio y el hábito los factores que ejercen influencia, mas no la etiqueta (Boztug et al, 2015).…”
Section: Etiquetado Y Su Impacto En El Consumo De Sal Azúcar Y Grasaunclassified